Low-Temperature Heat Capacities and Thermal Stability of New Antidepressant [5-Amino-4-(3-indoly)-3-methyl Pyrazole] - Fan, Mei-Qiang; Sun, Li-Xian; Xu, Fen (Asian Journal of Chemistry, 2010)
Low-temperature heat capacities of 5-amino-4-(3-indoly)-3-methyl pyrazole were measured by a temperature modulated differential scanning calorimetry in the temperature range from T = 193 to 503 K. An obvious endothermic process took place in the temperature range of 463-483 K. The peak in the heat capacity curve was correspondent to the fusion. The experimental molar heat capacities in the temperature range of 243-443 K were fitted to the polynomial. The peak temperature, molar enthalpy and entropy of the phase change had been determined to be 476 K, 27.618 kJ mol-1 and 58.389 J mol-1 k-1 by the repeated heat capacity measurements in the temperature region of 193-503 K. The thermodynamic functions, (HT-H298.15 K) and (ST-S298.15 K), of the compound had been calculated by the numerical integral of the heat-capacity polynomial. In addition, TG-DTG techniques were used for further study of thermal behaviour of the compound and showed that the compound began to decompose at 500 K.